1992
DOI: 10.1007/bf00301010
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome abnormalities in peripheral lymphocytes from patients with progressive systemic sclerosis

Abstract: Chromosomal abnormalities in cultured peripheral lymphocytes from 14 progressive systemic sclerosis (PSS) patients and 15 normal subjects were examined. No increase was observed in the frequency of chromosome aberrations in PSS patients who had not received any medical treatment. Those who had received medication showed an increased frequency of dicentrics (0.3%) although the frequency was not significantly higher than that for normal subjects. It is not clear, however, whether the increase was due to the hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…Wolff et al [ 103 ] observed that SSc lymphocytes exhibited a generalized susceptibility to DNA damage by free radicals either spontaneously or medication-induced. This observation was further supported by Takeuchi et al [ 104 ]. Roberts-Thomson et al [ 105 ] found that SSc exhibited a higher proportion of mitotic recombination mutations supporting the acquired genetic damage in SSc patients.…”
Section: The Molecular Basis Of Accelerated Inflamm-aging In Patients With Sscsupporting
confidence: 79%
“…Wolff et al [ 103 ] observed that SSc lymphocytes exhibited a generalized susceptibility to DNA damage by free radicals either spontaneously or medication-induced. This observation was further supported by Takeuchi et al [ 104 ]. Roberts-Thomson et al [ 105 ] found that SSc exhibited a higher proportion of mitotic recombination mutations supporting the acquired genetic damage in SSc patients.…”
Section: The Molecular Basis Of Accelerated Inflamm-aging In Patients With Sscsupporting
confidence: 79%
“…A Japanese study 8 reported an increase in chromosome abnormalities in a group of medically treated SSc patients with respect to nontreated ones, although the difference in damage frequency was not significant between these groups. As a consequence, the results of the present study may indicate that the presence of chromosome abnormalities in our patient may be an effect of previous immunosuppressive therapy rather than one of the manifold causes of susceptibility towards disease.…”
Section: Discussionmentioning
confidence: 90%